2021
DOI: 10.1155/2021/5548746
|View full text |Cite
|
Sign up to set email alerts
|

Oral Candidal Load and Oral Health Status in Chronic Obstructive Pulmonary Disease (COPD) Patients: A Case-Cohort Study

Abstract: Objective. The objective of this study was to determine the candidal load of the patients with Chronic Obstructive Pulmonary Disease (COPD) and evaluate the oral health status of subjects with COPD. Material and Methods. N = 112 COPD subjects and N = 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Most previous studies have focused on one or two indicators, such as periodontitis or the number of permanent teeth. 9 11 21 33 34 Additionally, Gaeckle and colleagues 35 recently showed that compared with healthy controls, participants with COPD had fewer teeth, a trend of a higher plaque index, and worse oral health-related quality of life. However, the study was limited by its small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies have focused on one or two indicators, such as periodontitis or the number of permanent teeth. 9 11 21 33 34 Additionally, Gaeckle and colleagues 35 recently showed that compared with healthy controls, participants with COPD had fewer teeth, a trend of a higher plaque index, and worse oral health-related quality of life. However, the study was limited by its small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…This inhaled medication can impact dental and oral health depending on the dose, frequency, and duration of use. (16) Conditions that are often encountered due to long-term side effects of inhaled drugs are xerostomia, dental caries, oral candidiasis, gingivitis, impaired sense of taste, and periodontitis. The underlying pathophysiology is the presence of inhaled drug residues in the oral cavity and oropharynx.…”
Section: Impact Of Copd On Oral Health Problemsmentioning
confidence: 99%
“…Khijmatgar et al reported that oral Candida was more common in the COPD group than in the controls (21.42% vs. 1.1%). They also observed higher DMFT and significant caries index scores in patients with COPD [ 98 ].…”
Section: Biological Mechanisms Underlying This Relationshipmentioning
confidence: 99%
“…Anticholinergics may also decrease salivary production and can interfere with the clearance of oral bacteria [ 113 ]. Theophylline medication can be a risk factor for increased candidal load in patients with COPD [ 98 ].…”
Section: Biological Mechanisms Underlying This Relationshipmentioning
confidence: 99%